PENGARUH PAJAK DAERAH, DANA ALOKASI UMUM (DAU) DAN DANA ALOKASI KHUSUS (DAK) TERHADAP BELANJA MODAL DI PROVINSI BALI PERIODE 2016-2020 - Muhammad Naufal Rifqi Aldya; Rino Rinaldo; Elvia Fardiana (Asosiasi Dosen Muda Indonesia, 2023)
The purpose of this study is to find out and analyze whether Regional Taxes, General Allocation Funds and Special Allocation Funds affect Capital Expenditures in the Provincial Government of Bali for the 2016-2020 period. The research variables used consist of independent variables, namely Regional Taxes, General Allocation Funds and Special Allocation Funds and the dependent variable, namely Capital Expenditures. The analytical method used is the multiple regression test, hypothesis testing, namely the t-test and F-test and the Coefficient of Determination Test. Based on the results of the study, it shows that partially Regional Taxes and Special Allocation Funds have an effect on Capital Expenditures, while General Allocation Funds have no effect on Capital Expenditures. Simultaneous test results show that Regional Taxes, General Allocation Funds and Special Allocation Funds have an effect on Capital Expenditures. Keywords: Regional Tax, General Allocation Fund, Special Allocation Fund, Capital Expenditure